"It's Not Me, It's Not Really Me." Insights From Patients on Living With Systemic Sclerosis: An Interview Study. Issue 11 (9th October 2017) - Sumpton, Daniel; Thakkar, Vivek; O'Neill, Sean; Singh‐Grewal, Davinder; Craig, Jonathan C.; Tong, Allison
Abstract : Objective: Patients with systemic sclerosis (SSc) experience severe physical limitations and psychological morbidity, but their lived experience remains underrepresented and is reflected in the scarcity of evidence‐based patient‐centered interventions. We aimed to describe patients' perspectives of SSc to inform strategies to improve their care. Methods: Face‐to‐face semistructured interviews were conducted with 30 adult patients with limited cutaneous or diffuse cutaneous SSc in Australia. Transcripts were thematically analyzed using HyperRESEARCH software. Results: Six themes were identified: bodily malfunction (restrictive pain, debilitating physical changes, pervasive exhaustion), deprivation of social function (loss of work and career, social isolation, threat to traditional roles, loss of intimacy), disintegration of identity (stigmatizing physical changes, disassociated self‐image, extinguished hopes, alone and powerless, invisibility of illness), insecurity of care (unrecognized disease, ambiguity around diagnosis and cause, information insufficiency, resigning to treatment limitations, seeking reassurance, fear of progression), avoiding the sick role (evading thoughts of sickness, protecting family, favorable comparison), and perseverance and hope (positive stoicism, optimism about treatment and monitoring, taking control of own health, pursuing alternative treatments, transcending illness through support). Conclusion: SSc inflicts major bodily and social restrictions that crush patients' identity and self‐image. Uncertainties about the cause, diagnosis, and prognosis can undermine confidence in care, leading to anxiety and therapeutic nihilism. Access to psychosocial care to support the patients' role and functioning capacity, as well as communication and education that explicitly address their concerns regarding management may potentially improve treatment satisfaction, self‐efficacy, adherence, and outcomes in patients with SSc.